2001
DOI: 10.1038/35083567
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ultraviolet radiation on the vertical distribution of zooplankton of the genus Daphnia

Abstract: The vertical migration of zooplankton into lower and darker water strata by day is generally explained by the avoidance of visually orienting predators, mainly fish; however, it is unclear why daily zooplankton migration has been maintained in fishless areas. In addition to predation, ultraviolet radiation-a hazardous factor for zooplankton in the surface layers of marine and freshwater environments-has been suspected as a possible cause of daytime downward migration. Here we test this hypothesis by studying s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
194
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(202 citation statements)
references
References 26 publications
4
194
1
3
Order By: Relevance
“…For example, while the freshwater cladoceran Daphnia often exhibits a strong UV avoidance response, this is often not true for freshwater and some marine copepods that may even be attracted to UV. Experiments in 0.5-1-m-deep columns that manipulated UV under both artificial and natural solar light sources showed that UV stimulates a downward migration in several species of Daphnia (Hessen 1994;Rhode et al 2001). On the other hand, the copepod Cyclops serrulatus shows only a slight (statistically untested) preference for visible light over UV-B (Barcelo and Calkins 1979).…”
mentioning
confidence: 99%
“…For example, while the freshwater cladoceran Daphnia often exhibits a strong UV avoidance response, this is often not true for freshwater and some marine copepods that may even be attracted to UV. Experiments in 0.5-1-m-deep columns that manipulated UV under both artificial and natural solar light sources showed that UV stimulates a downward migration in several species of Daphnia (Hessen 1994;Rhode et al 2001). On the other hand, the copepod Cyclops serrulatus shows only a slight (statistically untested) preference for visible light over UV-B (Barcelo and Calkins 1979).…”
mentioning
confidence: 99%
“…Nonetheless, planktonic animals have different biological strategies for dealing with natural doses of UV-B light. One strategy is the avoidance of harmful radiation via behavioral mechanisms, such as diel vertical migration (Siebeck and Böhm 1994;Leech and Williamson 2001;Rhode et al 2001). Other strategies include those that confer tolerance to UV light (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such migratory behaviour, i.e. avoiding surface waters during the day, observed in the absence of fish is most probably caused by ultraviolet radiation, an important factor shaping zooplankton vertical distribution in high altitude or latitude ultraoligotrophic habitats (Tartarotti et al, 1999;Rhode et al, 2001;Williamson et al, 2001), preventing the animals from fully profiting from higher temperatures in the subsurface water during daylight hours. The between-year variability in depth and temperature distribution is interrelated, depth of occurrence being influenced by temperature profile and other resulting physical and biotic gradients in the lake.…”
Section: Discussionmentioning
confidence: 99%